2020
DOI: 10.1021/acscatal.0c01582
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylate-Assisted β-(Z) Stereoselective Hydrosilylation of Terminal Alkynes Catalyzed by a Zwitterionic Bis-NHC Rhodium(III) Complex

Abstract: The zwitterionic compound [Cp*RhCl{(MeIm)2CHCOO}] is an efficient catalyst for the hydrosilylation of terminal alkynes with excellent regio-and stereoselectivity towards the less thermodynamically stable β-(Z)-vinylsilane isomer under mild reaction conditions. A broad range of linear 1-alkynes, cycloalkyl acetylenes and aromatic alkynes undergo the hydrosilylation with HSiMe2Ph to afford the corresponding β-(Z)-vinylsilanes in quantitative yields in short reaction times. The reaction of aliphatic alkynes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 92 publications
(91 reference statements)
0
12
0
Order By: Relevance
“…In a recent contribution, Pérez-Torrente, Jiménez, et al have reported zwitterionic rhodium complex [Cp*RhCl-{(MeIm) 2 CHCOO}], 40 , which catalyses the regio- and stereoselective hydrosilylation of terminal alkynes, yielding β-( Z )-vinylsilanes (Scheme 41). 91 They provided evidence (by means of DFT calculations, isotopic labelling and mass spectrometry) for a catalytic system working through an outer-sphere mechanism. The carboxylate group plays a key role by temporarily trapping an “R 3 Si + ” fragment from a σ-SiH iridium complex (intermediate T , η 1 -coordination mode) and transferring it to the terminal alkyne.…”
Section: Catalytic Silylation Reactionsmentioning
confidence: 99%
“…In a recent contribution, Pérez-Torrente, Jiménez, et al have reported zwitterionic rhodium complex [Cp*RhCl-{(MeIm) 2 CHCOO}], 40 , which catalyses the regio- and stereoselective hydrosilylation of terminal alkynes, yielding β-( Z )-vinylsilanes (Scheme 41). 91 They provided evidence (by means of DFT calculations, isotopic labelling and mass spectrometry) for a catalytic system working through an outer-sphere mechanism. The carboxylate group plays a key role by temporarily trapping an “R 3 Si + ” fragment from a σ-SiH iridium complex (intermediate T , η 1 -coordination mode) and transferring it to the terminal alkyne.…”
Section: Catalytic Silylation Reactionsmentioning
confidence: 99%
“…The β-Z selective hydrosilylation of terminal alkynes were dominated by noble metal catalysts, especially Rh ( 3, entries 9 and 10). [78][79] Both Ir(I) and Ir(III) complexes were prove to be suitable catalysts for β-Z selective hydrosilylation of alkynes (Table 3, entries 11-16). [80][81][82][83][84][85][86] The hard-basic ligands with N, O, C as coordinative groups seems suitable for Ir catalysts.…”
Section: Noble Metal Catalysts (Table 3)mentioning
confidence: 99%
“…Although the reactivity and mechanism of metal–ligand cooperative Si–H bond cleavage have thus far been intensively studied, reports on its application in catalytic reactions are still limited, such as hydrosilylation of acetophenone by group 9 metal thiolates, other reactions catalysed by a cationic ruthenium thiolate complex, and hydrosilylation of terminal alkynes catalysed by a bis-NHC rhodium complex. 9–12…”
Section: Introductionmentioning
confidence: 99%